The psychology of diversity and its implications for workplace (in)equality: Looking back at the last decade and forward to the next. Issue 3 (21st March 2022) - Fletcher, Luke; Beauregard, T. Alexandra
Abstract: In this British Psychological Society (BPS) landmark paper, we employ an evidence synthesis approach to review the broad range of diversity research published in BPS journals between 2011 and 2021. By focusing on research that investigates stereotypes associated with, and discrimination towards, minority and minoritized groups, we seek to provide readers with a better understanding of the dynamics of a diverse workforce and, going forward, to facilitate the efforts of the psychology research community towards building a body of work that meaningfully addresses workplace inequalities. We thematically analyse and synthesize 25 articles, which fall into four interconnected themes: identity development and management; negative stereotypes, prejudice, and discrimination; working in a diverse team; and the broader organizational environment. Highlighting key strengths of this work and areas for future development, we note the absence of overarching theoretical debates and discussions that might facilitate the development of an on‐going narrative across diversity‐related research published within BPS journals. We outline a future research agenda to bridge methodological divides and to connect with diversity literatures in related disciplines such as human resource development (HRD), human resource management (HRM), and organization studies. In so doing, we advocate for psychologists to move beyond a solely individualistic perspective and instead recognize and account for the context within which diversity‐related processes take place.